A novel microdeletion upstream of HOXD13 in a Chinese family with synpolydactyly. Issue 1 (31st August 2021) - Jia, Weimin; Zhou, Xiaopei; Guo, Naiqiang; Zhang, Dazhi; Hou, Meiqi; Luo, Yalin; Peng, Xuejie; Yang, Xue; Zhang, Xianqin
Abstract: Synpolydactyly (SPD) is a digital malformation with the typical clinical phenotype of the webbing of 3/4 fingers and/or 4/5 toes, and combined with polydactyly. In this study, we investigated a Chinese family with SPD and genetic analysis found that all of the affected individuals in the family carry a heterozygous 11, 451 bp microdeletion at chr2:176933872‐176945322 (GRCh37), which is located upstream of HOXD13 gene, the known disease gene for SPD1. All the affected individuals in the family carry the heterozygous deletion variant, and the variant co‐segregated with SPD in the family. Thus, we speculate that the 11, 451 bp microdeletion is the disease‐causing variant in the family. To date, the microdeletion associating with SPD1 which we identified is the smallest deletion upstream of the HOXD13 gene and not altering the sequence of the HOXD13 gene.